Dynamic expression of broad-complex isoforms mediates temporal control of an ecdysteroid target gene at the onset of Drosophila metamorphosis. - Mugat, B.; Brodu, V.; Kejzlarova-Lepesant, J.; Antoniewski, C.; Bayer, C.A.; Fristrom, J.W.; Lepesant, J.A. (Developmental Biology, 2000)
Metamorphosis in Drosophila melanogaster is orchestrated by the steroid hormone ecdysone, which triggers a cascade of primary-response transcriptional regulators and secondary effector genes during the third larval instar and prepupal periods of development. The early ecdysone-response Broad-Complex (BR-C) gene, a key regulator of this cascade, is defined by three complementing functions (rbp, br, and 2Bc) and encodes several distinct zinc-finger-containing isoforms (Z1 to Z4). Using isoform-specific polyclonal antibodies we observe in the fat body a switch in BR-C isoform expression from the Z2 to the other three isoforms during the third instar. We show that the 2Bc(+) function that corresponds presumably to the Z3 isoform is required for the larval fat body-specific expression of a transgenic construct (AE) in which the lacZ gene is under the control of the ecdysone-regulated enhancer and minimal promoter of the fat body protein 1 (Fbp1) gene. Using hs(BR-C) transgenes, we demonstrate that overexpression of Z1, Z3, or Z4, but not Z2, is able to rescue AE activity with faithful tissue specificity in a BR-C null (npr1) genetic context, demonstrating a partial functional redundancy between Z1, Z3, and Z4 isoforms. We also show that continuous overexpression of Z2 during the third instar represses AE, while conversely, expression of Z3 earlier than its normal onset induces precocious expression of the construct. This finding establishes a tight correlation between the dynamic pattern of expression of the BR-C isoforms and their individual repressive or inductive roles in AE regulation. Altogether our results demonstrate that the balance between BR-C protein isoforms in the fat body mediates, in part, the precise timing of the ecdysone activation of the AE construct but does not modulate its tissue specificity.